2017
DOI: 10.1016/j.expneurol.2017.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Refining environmental enrichment to advance rehabilitation based research after experimental traumatic brain injury

Abstract: The typical environmental enrichment (EE) paradigm, which consists of continuous exposure after experimental traumatic brain injury (TBI), promotes behavioral and histological benefits. However, rehabilitation is often abbreviated in the clinic and administered in multiple daily sessions. While recent studies have demonstrated that a once daily 6-hr bout of EE confers benefits comparable to continuous EE, breaking the therapy into two shorter sessions may increase novelty and ultimately enhance recovery. Hence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…ARIP, unlike haloperidol, has no D 2 antagonist effects, but instead functions as a partial D 2 and 5-HT 1A receptor agonist (Burris et al, 2002;Wood and Reavill, 2007;Tanahashi et al, 2012). The hypothesis was that ARIP would confer cognitive benefits when provided alone, as previously shown (Phelps et al, 2017), but the benefits would be further enhanced when combined with EE, a preclinical model of neurorehabilitation (Kline et al, 2010;Bondi et al, 2014bBondi et al, , 2015Radabaugh et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ARIP, unlike haloperidol, has no D 2 antagonist effects, but instead functions as a partial D 2 and 5-HT 1A receptor agonist (Burris et al, 2002;Wood and Reavill, 2007;Tanahashi et al, 2012). The hypothesis was that ARIP would confer cognitive benefits when provided alone, as previously shown (Phelps et al, 2017), but the benefits would be further enhanced when combined with EE, a preclinical model of neurorehabilitation (Kline et al, 2010;Bondi et al, 2014bBondi et al, , 2015Radabaugh et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It has been speculated in the past that the robust benefits consistently achieved with continuous EE provides a floor effect that limits recovery beyond a certain threshold. To remedy this potential discrepancy and to optimize EE as a viable preclinical model of neurorehabilitation, we have begun to delay the administration and limit the amount of EE provided to rats after TBI (Matter et al, 2011;de Witt et al, 2011;Radabaugh et al, 2016Radabaugh et al, , 2017Lajud et al, 2018). An interesting and informative future direction would be to evaluate ARIP combined with the optimized (i.e., more clinically relevant) EE paradigm to determine if an additive effect may emerge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This nurturing environment is demonstrated to improve social ability, spatial cognition, and brain plasticity in healthy animals ( Fares et al, 2013 ; Hannan, 2014 ; Garthe et al, 2016 ). EE also exerts positive effects on various animal models of neurological disorders including AD ( Wolf et al, 2006 ; Salmin et al, 2017 ), Parkinson’s disease ( Hilario et al, 2016 ), stroke ( Livingston-Thomas et al, 2016 ), traumatic brain injury ( Radabaugh et al, 2017 ), and Huntington’s disease ( Skillings et al, 2014 ). EE includes not only physical factors, such as exercise and sensorial and visual stimulations, but also improved social interaction between individuals ( Van Praag et al, 2000 ; Nithianantharajah and Hannan, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in an experimental laboratory setting it was observed that 6-hours of environmental enrichment provision on a daily basis was effective in conferring neurobehavioral and histological amelioration following TBI with extended improvements through the realization that the acquired benefits were comparable despite the manner in which the 6-hours of enriched environment were accrued [20]. The development of coping strategies for thriving and disorder adaptation, as well as the psychological adaptation to stressors and serious life events, have been discover to exert a marked influence on the progressive improvement and against the persistence of posttraumatic injury complaints.…”
Section: Introductionmentioning
confidence: 99%